2021
DOI: 10.31004/basicedu.v5i6.1593
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Teachers’ Continuing Professional Development (CPD) : Teachers’ Reflection of Expectation and Reality

Abstract: Teachers’ quality plays a paramount role in the improvement of quality of education. This paper describes the reflection of expectation and reality from the concept and the implementation of CPD of Primary School teacher in Indonesia. The objectives of CPD are increasing teachers’ professional development, increasing education services and upgrading professional qualification. In Indonesia, the objectives CPD only touches increasing education services and professional development. Teachers should involve in CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…(Kastawi & Yuliejantiningsih, 2019) showed that only 5% of teachers were actively participating in CPD activities and only 4% of teachers set aside teacher certification to participate in teacher CPD activities. This is in line with (Agusta & Kristiawan, 2021) showing that only 12.5% of teachers are always active in CPD participation in participating in scientific publications and innovative works.…”
Section: Introductionsupporting
confidence: 89%
“…(Kastawi & Yuliejantiningsih, 2019) showed that only 5% of teachers were actively participating in CPD activities and only 4% of teachers set aside teacher certification to participate in teacher CPD activities. This is in line with (Agusta & Kristiawan, 2021) showing that only 12.5% of teachers are always active in CPD participation in participating in scientific publications and innovative works.…”
Section: Introductionsupporting
confidence: 89%
“…The program was running with the activity without the assessment clearly. These became considered for the input of a hypothetical model (Agusta & Kristiawan, 2021).…”
Section: Discussionmentioning
confidence: 99%